Telehealth in the Context of COVID-19: Changing Perspectives in Australia, the United Kingdom, and the United States - Fisk, Malcolm; Livingstone, Anne; Pit, Sabrina Winona (Journal of medical Internet research, 2020)
On March 12, 2020, the World Health Organization declared the coronavirus disease (COVID-19) outbreak a pandemic. On that date, there were 134,576 reported cases and 4981 deaths worldwide. By March 26, 2020, just 2 weeks later, reported cases had increased four-fold to 531,865, and deaths increased five-fold to 24,073. Older people are both major users of telehealth services and are more likely to die as a result of COVID-19. This paper examines the extent that Australia, the United Kingdom, and the United States, during the 2 weeks following the pandemic announcement, sought to promote telehealth as a tool that could help identify COVID-19 among older people who may live alone, be frail, or be self-isolating, and give support to or facilitate the treatment of people who are or may be infected. This paper reports, for the 2-week period previously mentioned and immediately prior, on activities and initiatives in the three countries taken by governments or their agencies (at national or state levels) together with publications or guidance issued by professional, trade, and charitable bodies. Different sources of information are drawn upon that point to the perceived likely benefits of telehealth in fighting the pandemic. It is not the purpose of this paper to draw together or analyze information that reflects growing knowledge about COVID-19, except where telehealth is seen as a component. The picture that emerges for the three countries, based on the sources identified, shows a number of differences. These differences center on the nature of their health services, the extent of attention given to older people (and the circumstances that can relate to them), the different geographies (notably concerned with rurality), and the changes to funding frameworks that could impact these. Common to all three countries is the value attributed to maintaining quality safeguards in the wider context of their health services but where such services are noted as sometimes having precluded significant telehealth use. The COVID-19 pandemic is forcing changes and may help to establish telehealth more firmly in its aftermath. Some of the changes may not be long-lasting. However, the momentum is such that telehealth will almost certainly find a stronger place within health service frameworks for each of the three countries and is likely to have increased acceptance among both patients and health care providers.